Comparative evaluation of the effect of microfluidisation on physicochemical properties and usability as food thickener and Pickering emulsifier of autoclaved and TEMPO-oxidised nanofibrillated cellulose - Sirada Sungsinchai (2022)
Although chemical-free production processes of nanofibrillated cellulose (NFC) have been investigated, comparative studies on the effect of chemical and chemical-free processes to produce NFCs are limited. Combined effect of either of these production routes and defibrillation condition has also never been studied. Here, thermally treated NFCs were produced through microfluidisation for 6–12 passes (ANFC6-ANFC12), while TEMPO-oxidised NFC (TONFC) was prepared at six passes. Proportion of nanocellulose, viscosity, Gʹ and Gʺ values increased with increased microfluidisation pass in the cases of ANFCs. ANFC12 exhibited gel-like behaviour with strongest three-dimensional network structure and required lowest concentration to enhance thin liquid foods into honey-like consistency. TONFC needed to be added by as much as 8.5, 1.3 and 2.3 times the amount of ANFC12 to achieve the same consistency in thickened water, milk and soup, respectively. ANFC12 can also be well used as Pickering emulsifier due to its higher viscosity and gel-like property.